The Influences of Green Packaging and Ecolabel Toward Green Purchase Intention - Hanifa Nur Fadhilla; Murwani Eko Astuti (Journal of Business and Behavioural Entrepreneurship, 2022)
This study aims to analyze the effect of green packaging and ecolabel on green purchase intention specifically The Body Shop survey products. The sampling technique used is purposive sampling with the following criteria: consumers who are interested in purchasing green products, more than 18 years old, have a minimum education of high school, and purchase at least one-time product of The Body Shop. The number of respondents there are 103 respondents. The data collection method used is questionnaires with a likert scale that has been tested and has met the validity and reliability requirements. The analytical technique used is SPSS. The result of this research expressed that from two independent variables particularly green packaging and ecolabel have positive significance influence toward green purchase intention. Hypotheses are accepted. This research result derives from t-test statistics.